2014
DOI: 10.5958/2348-7542.2014.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source and sink removal on yield attributes and yield of mungbean [Vigna radiata(L.) Wilczek]

Abstract: Field experiments were conducted to investigate the effect of source (leaf) and sink (flower and pod) removal on some morphological characters, and yield and its attributes in high and low yielding mungbean genotypes grown under sub-tropical condition. Four levels of defoliation (0, 8, 16 and 33%), four levels of deflowering (no deflowering, deflowering of all opened flowers borne up to 10th or 15th or 20th nodes in a raceme), and four levels of depodding (no depodding, depodding of all pods for 5 or 10 or 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This also indicated that high yielding genotypes has higher compensatory mechanism to source (leaf) loss than low yielding ones. Similar statement about compensatory mechanism of low and high yielding genotypes has earlier been reported [7][8] also stated that 25 per cent defoliation not affects the significant yield loss but slightly enhance the yield in mungbean. The higher leaf compensation capacity in high yielding genotype could be due to higher number of newly emerged leaves and their high phososythetic activity after defoliation may accumulate more sink resulting higher yield up to threshold level.…”
Section: Resultssupporting
confidence: 65%
“…This also indicated that high yielding genotypes has higher compensatory mechanism to source (leaf) loss than low yielding ones. Similar statement about compensatory mechanism of low and high yielding genotypes has earlier been reported [7][8] also stated that 25 per cent defoliation not affects the significant yield loss but slightly enhance the yield in mungbean. The higher leaf compensation capacity in high yielding genotype could be due to higher number of newly emerged leaves and their high phososythetic activity after defoliation may accumulate more sink resulting higher yield up to threshold level.…”
Section: Resultssupporting
confidence: 65%
“…In Bogra the moisture content of farmers saved seeds ranged from 12.30 to 14.40% [20]. The moisture content of farmers' seeds collected from Rajshahi, Bogra and Rangupur reported ranged from 7.0 to 13.9% that varying with respect to crop season farmers and location of seed collection, But in 2003 they reported that the moisture content of farmers' rice of the same locations ranged from 12.87% to 13.30% [12]. It indicates that moisture content may vary from farmers to farmers as well as location to location.…”
Section: Effect Of Storing Containers On Moisture Content Of Seed Sammentioning
confidence: 99%
“…Another study shown that the moisture content and black point infection increased, the seed germination decreased with the increase of storage period [13]. Reported that number of insect damage seeds, insect population and fungi infection varied with respect to storage containers, storage period and additives used [3,12]. It was showed that gunny bag is the worst compare to metal structures as storage containers for ensuring quality of seeds [13] and also reported that highest germination and lowest prevalence of fungi were recorded in the seeds stored in tin followed by polythene bag and gunny bag with polythene lining [20].…”
Section: Effect Of Storing Containers On Apparantly Healty Seeds and mentioning
confidence: 99%